Diversity in higher education: Students' grits and fears - Santos, G.; Dias, D.; Candeias, T.; Pinto da Costa, E.; Justino, E. (EDULEARN23 Proceedings, 2023)
Framework: Demographic changes, which have taken on a new paradigm after the COVID-19 pandemic, have led researchers to approach diversity with a focus on gaining a competitive advantage. Therefore, one of the objectives is to obtain knowledge regarding the new generations in the changing landscape of education, which requires attention to the needs of teaching a multicultural audience (Unruh & McCord, 2010). With globalization and the migration of people from different backgrounds to different countries, classrooms are becoming increasingly diverse, which means that teachers need to be prepared to work with students who have different cultural, linguistic, and socioeconomic backgrounds, as well as different experiences and learning styles. In this sense, it becomes urgent to get to know the students who make up the University, so that we can understand the diversity in each of the domains that make up the MGUD-S scale, in the dimensions of Diversity of Contact with others, Relativistic Appreciation, and Comfort with Differences, which require adequate measurement of attitudes and dispositions towards diversity. Objective: Our aim is to validate the Miville-Guzman Universality-Diversity Scale (MGUD-S) for the Portuguese population, specifically for higher education students, and it has been applied in institutions of higher education in Portugal in the field of Social Sciences. Methodology: During the period from November 2021 to January 2022, the survey was administered to 820 students from various academic programs and courses, during a time of adaptation to the new reality of physical presence in classrooms. The MGUD-S scale comprises three subscales that evaluate the corresponding dimensions of Diversity of Contact, Relativistic Appreciation, and Comfort with Differences. Structural equation modeling, specifically confirmatory factor analysis, was employed to validate the adaptation and translation of the scale. Results: The final sample consisted of 820 Portuguese university students from the Social Sciences area. In terms of age range, 54.1% belonged to the 17-20 age group, while 37.3% were from the 21-25 age group. 83.4% were Portuguese, 7.9% were from African countries, and 7.6% were Brazilian. 88.4% were undergraduate students, and 11.1% were graduate students. Regarding gender, females predominated with 62.2%. The factorial validity of the Portuguese adaptation of the MGUDS-Short Form scale was performed, and the three-factor model was composed of 14 out of the original 15 items, showing reasonable goodness-of-fit. Implications: We believe that the validation of the MGUD-S scale for the Portuguese language is crucial to measure and understand attitudes and dispositions towards cultural and linguistic diversity among higher education students in Portugal. Understanding students' diversity is essential to promote an inclusive and welcoming classroom environment, which can have a significant impact on academic success and student satisfaction. Furthermore, adapting teaching methods and materials to meet the needs of students from different cultural and linguistic backgrounds can improve the quality of education and prepare students for the increasingly diverse and globalized world we live in.